Pengaruh Kualitas Pelayanan Akademik terhadap Kepuasan Mahasiswa Universitas Negeri Padang - Wahib Assyahri; Mardaus Mardaus (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
The purpose of this study was to analyze the effect of the academic service quality on the students’ satisfaction of Universitas Negeri Padang. There were still students of Universitas Negeri Padang which were complaining about the services that they found to be unsatisfactory was the background of this study. The research method which was used was a quantitative research method. The population in this study were the Universitas Negeri Padang’s students that have a year of entry in 2018 and 2020. The sample in this study used the Slovin formula with an error rate was 10% and it produced 100 samples of students. In addition, the determination of the sample in this study was carried out by using the Proportionate Stratified Random Sampling technique. Data collection technique which was used was a questionnaire that was distributed to the respondents with its measurement by using a Likert scale. After the data obtained, it was analyzed by using simple linear regression. The result of this research showed that (1) The variable quality of academic service has a significant effect on the satisfaction of Universitas Negeri Padang’s students simultaneously with a significance value was 0,000 and the an adjusted R Square value was 0.681. Thus, the effect of the academic service quality on the students’ satisfaction at Universitas Negeri Padang was 68.1%. (2) The test result partially, tangible sub-variable, responsiveness, and empathy, it influenced significantly the students’ satisfaction.